Ethics and futures studies. (17th January 2012) - Poli, Roberto
Ethics and futures studies interact in at least three ways: 1) through the values present within a foresight exercise; 2) through the understanding that values require the dimension of the future; 3) through the problem of the deontological code of the futurist. (1) and (3) characterise the work of the futurist; (2) instead proceeds in reverse: the need to address the question of the future arises from within ethics itself.